Production of methane gas by Ultrasonic Membrane Anaerobic System (UMAS) using sewage sludge as substrate - Nabila Hakim, Mohamad Asri (2013)
A study was conducted to verify the status of the application of Ultrasonic Membrane Anaerobic System(UMAS) in wastewater treatment,efficiency of UMAS in methane production and kinetic parameters in sewage sludge on methane production from sewage sludge by using UMAS.UMAS consist of Ultrafiltration membrane for solid-liquid separation with 1.5 – 2.0 bar of operational pressure. The wastewater has been extensively analyzed for six parameters which are pH value, biochemical oxygen demand(BOD),chemical oxygen demand(COD),volatile fatty acids(VFA),total suspended solid(TSS)and volatile suspended solid (VSS).The reactor is operated at ambient temperature and wrapped with aluminum foil to avoid direct sunlight,which can affect the bacteria. The raw sewage sludge was obtained from Indah Water Air Putih, Kuantan.Sewage sludge is tested using jar test for the chemical requirements to remove small particles in the waste water.The digester operates 5 hours every 4 days for 12 days.The product that been produce contained carbon dioxide and methane gas.Both gases are collected into a syringe that connected with two rubber tube and a glass tube. Compare to aerobic digestion which is expensive method since it used oxygen and anaerobic digestion that requires larger area and slower process,UMAS was being innovated and offer great advantages.Carbon dioxide is removed by manipulated the syringe using 10 ml of sodium hydroxide. Methane gas is measured once every four days.This treatment showed the best solution to treat waste water such as reduction of COD contents and increased percentage of methane gas.Thus,make UMAS is a good alternative for treating wastewater.